1991
DOI: 10.1037/h0094322
|View full text |Cite
|
Sign up to set email alerts
|

A brief perspective on Calvin Hall: Commentary on Hall's paper.

Abstract: Calvin Hall's contributions have not always been properly appreciated. Hall set forth a cognitive theory of dreams as early as 1953.To Hall, dreaming is a cognitive process and the images of a dream are "the embodiment of thoughts." Hall felt that dreams illuminate the basic conflicts and predicaments conceptualized by the dreamer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 4 publications
0
14
1
Order By: Relevance
“…Mayer's text remains primary, but we now begin with an overview of Kuhn's (1962Kuhn's ( , 2012 theory of scientific revolutions so that students have a framework for understanding the paradigmatic implications of the data they will be studying for the next 10 weeks. They also read Moody's book, Life after Life (1975Life ( , 2001, an article by Van Lommel (2006) summarizing his prospective near-death research, and two chapters by Van de Castle (1994) about the relevance of dreams to understanding and exploring consciousness. In addition, they watch a variety of films and talks by Ken Wilber, Dean Radin, Rupert Sheldrake, and others that extend and amplify the topics discussed in the texts.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mayer's text remains primary, but we now begin with an overview of Kuhn's (1962Kuhn's ( , 2012 theory of scientific revolutions so that students have a framework for understanding the paradigmatic implications of the data they will be studying for the next 10 weeks. They also read Moody's book, Life after Life (1975Life ( , 2001, an article by Van Lommel (2006) summarizing his prospective near-death research, and two chapters by Van de Castle (1994) about the relevance of dreams to understanding and exploring consciousness. In addition, they watch a variety of films and talks by Ken Wilber, Dean Radin, Rupert Sheldrake, and others that extend and amplify the topics discussed in the texts.…”
Section: Methodsmentioning
confidence: 99%
“…Bruce Lipton (2005) and Emily Williams have explored the irrefutable power of the mind to affect the health of the body for good or for ill through psychophysiological influences such as placebos and nocebos, and Robert Jahn and Brenda Dunne demonstrated in over fifty million experimental trials that "operator consciousness is capable of inserting information, in its most rudimentary "objective" form, namely binary bits, into random physical systems, by some anomalous means" (quoted in Mayer, 2007, p. 243). Robert Van de Castle (1994) and Robert Waggoner (2009) have each shown that dreams are unique states of consciousness through which one can access sources of creativity, generate solutions to problems, and engage in wideranging explorations of different states of consciousness that cannot be perceived within the confines of the rational waking mind. And there is abundant clinical evidence from the neardeath studies of Raymond Moody (1975), Holden, Greyson, and James (2009) , Peter Fenwick and Elizabeth Fenwick (2008), Pim Van Lommel (2006, 2010, and Sam Parnia (2013) that consciousness appears to be more vigorous and unfettered after death than it is in life.…”
Section: All Paradigms Must Changementioning
confidence: 99%
“…Social interaction and interpersonal relationships, or interpersonal relationship characteristics, are other factors thought to have effect on dream themes and content (Hall & Nordby, 1972; Schweickert, 2007; Van de Castle, 1991). It is obvious that significant relationships and their objects are seen in dreams frequently.…”
mentioning
confidence: 99%
“…Interpersonal relationship style has been defined as forms of an individual’s experienced and internalized emotion, thoughts, and behaviors during relationships with others (Plutchik, 1997). Interpersonal relationships and conflicts that influence a great part of our lives as social beings are often reflected in our dreams (Van de Castle, 1991). Even though, during the literature review, no study was found emphasizing the direct links between defense mechanisms and interpersonal styles, there are findings pointing out that immature defense mechanisms have a disruptive effect on interpersonal relationships (Cramer, Blatt, & Ford, 1988; Perry & Cooper, 1992; Vaillant, 1992).…”
mentioning
confidence: 99%
“…It is offered here as one of a series of unpublished but still relevant manuscripts authored or co-authored by the late dean of systematic dream research within psychology in an attempt to connect this new journal with an earlier era of dream studies. The first of these manuscripts appeared in the initial issue of the journal along with three appreciations of Hall and his work (Hall, 1991;Domhoff, 1991;Kramer, 1991;Van de Castle, 1991).…”
mentioning
confidence: 99%